Packet Inter-arrival Time Distribution in Academic Computer Network - Garsva, E.; Paulauskas, N.; Grazulevicius, G.; Gulbinovic, L. (Elektronika ir Elektrotechnika, 2014)
The article presents the statistical analysis results of network packet inter-arrival time distribution in academic computer network. Most popular transport protocols TCP and UDP are addressed in the research. Data was gathered using NetFlow protocol. Network traffic was divided into sections according its direction and usage trends, then packet inter-arrival time distributions were found. Kolmogorov-Smirnov test was used to evaluate goodness-of-fit of packet inter-arrival time distributions and it was determined, that Pareto Second Kind distribution fits the majority of the experimental distributions. DOI: http://dx.doi.org/10.5755/j01.eee.20.3.6683